Raznojezičnost in medjezikovno razumevanje ter njuno vključevanje v učenje tujih jezikov - Mertelj, Darja (Vestnik za tuje jezike, 2017)
The paper offers some brief reviews about foreign/second languages teaching practices and their research regarding plurilingualism and intercomprehension, the latter meant as a support of pluri- and multilingualism in Europe, which has gained significantly increasing attention over the last twenty years. In the first part, higher education research and applied projects ("Jessner", "Gooskens", "Prokopowicz") regarding these topics that contributed to the improved comprehension of both phenomena and to the preparation of pluri- and multilinguistic syllabi proposals (for example CARAP / FREPA) are presented. Their main focus is placed within the frame of Germanic or Romance language families, or their combination with English. Directly or indirectly, the purpose of these projects is to develop intercomprehension and plurilingual education and techniques, and they also include related linguistic analyses. The review is followed by some examples from primary and secondary education (about plurilingual practices in the German area). In the second part of the paper, an example from a "plurilingual plus intercomprehension" platform is summarised - it is specifically designed according to principles of the development of intercomprehension and plurilingualism, which illustrates how "e-learning by e-doing" (intercomprehension in a chat room) can, for example, increase awareness about learners' own intercomprehension processes, plurilingual learning strategies and motivation.
Keywords: foreign language study and teaching; učenje in poučevanje tujih jezikov; didactic method; didactics; didaktika; multilingualism; večjezičnost; plurilingualism; raznojezičnost; intercomprehension; medjezikovno razumevanje; Germanic languages; germanski jeziki; Romance languages; romanski jeziki